2023
DOI: 10.1021/acsanm.2c05068
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Enhanced NO2 Sensing Based on the Hybrid Orthorhombic/Monoclinic-PdSe2 Nanostructures

Abstract: Palladium diselenide (PdSe2), as a member of two-dimensional dichalcogenides, has a puckered pentagonal structure and tends to exhibit distinct physical properties due to the various polymorphic phases. In contrast to conventionally orthorhombic PdSe2 (O-PdSe2), the fabrication of continuous metastable monoclinic PdSe2 (M-PdSe2) remains a challenge. Here, we report the polymorphic integration of orthorhombic and monoclinic PdSe2 crystals by concisely controlled selenization engineering under Se-sufficient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Therefore, the NO 2 , NO, and SO 2 gas molecules can strongly interact with the surfaces of monolayer MoS 2 , PdSe 2 , and graphene due to the comparable energies of the frontier molecular orbitals and band edges. Previous theoretical calculations and experiments confirm that these monolayer materials indeed can serve as promising gas sensors of NO 2 , NO, and SO 2 . ,,,,,, According to this screening criterion, unnecessary calculations can be avoided, and the appropriate adsorption gas molecules and substrate materials can be selected in advance, significantly saving the calculation time and accelerating the screening process.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Therefore, the NO 2 , NO, and SO 2 gas molecules can strongly interact with the surfaces of monolayer MoS 2 , PdSe 2 , and graphene due to the comparable energies of the frontier molecular orbitals and band edges. Previous theoretical calculations and experiments confirm that these monolayer materials indeed can serve as promising gas sensors of NO 2 , NO, and SO 2 . ,,,,,, According to this screening criterion, unnecessary calculations can be avoided, and the appropriate adsorption gas molecules and substrate materials can be selected in advance, significantly saving the calculation time and accelerating the screening process.…”
Section: Resultsmentioning
confidence: 94%
“…Previous theoretical calculations and experiments confirm that these monolayer materials indeed can serve as promising gas sensors of NO 2 , NO, and SO 2 . 5,6,11,25,26,54,55 According to this screening criterion, unnecessary calculations can be avoided, and the appropriate adsorption gas molecules and substrate materials can be selected in advance, significantly saving the calculation time and accelerating the screening process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in the structural and electronic properties of 2D materials may lead to different adsorption strengths, sensitivity, and selectivity of the resulting nano gas sensors. Choosing specific materials to detect and control target gas molecules can significantly improve the efficiency of the sensors. Previous works have shown that graphene can detect toxic gases, such as CO, NO, NO 2 , and NH 3 molecules. , However, phosphorene has a more significant band gap and electron mobility compared with graphene, which results in a higher affinity for gas molecules. , Its calculated gas adsorption energy and sensor sensitivity are significantly higher than graphene. Further studies have indicated that the gas selectivities of 2D materials may diversify greatly. Among graphene, silicene, phosphorene, and MoS 2 , MoS 2 has the highest adsorption intensity for CO molecule, , phosphorene has the most considerable adsorption energy of 0.86 eV for NO molecule, and silicene is the best for detecting NH 3 and NO 2 molecules …”
Section: Introductionmentioning
confidence: 99%